Legal Defense of Interethnic and Religious Relationships: Russian and International Experience - KUNTS, Elena; GOLUBOVSKII, Vladimir (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The objective of the paper consists in analyzing Russia's experience in legal defense of interethnic and religious relationships, in finding the approaches to smoothen the exacerbations in interethnic and religious relationships, and in identifying the place and role of conflicts between states, relying on the international experience in the above mentioned sphere of public relationships. The major method of the research is classification which was used in systematizing the infringements on interethnic and religious relationships. Generalization and analysis of criminal law norms were used for wording and justifying the theoretical provisions, practical recommendations and conclusions. The paper provides grounds for elaborating and efficient National policy strategy based on the civic patriotism, love for the Motherland, and respectful attitude towards the history of the state.